Market potential analysis of selected fruits in Southern Mindanao - Jaravelo, Lucia Erika H.; Digal, Larry N. (2004)
The study was conducted to analyze the market potential of selected fruits in Southern Mindanao, namely: banana, durian, mango, and pomelo. Key informant interviews were performed. Secondary data analysis was important in determining the market potential of the said fruits. The data used were obtained from several government agencies such as Bureau of Agricultural Statistics (BAS), National Statistical Coordination Board (NSCB), and the Philippine Institute for Development Studies (PIDS) Online Database. The income elasticity of demand and price elasticity of demand were computed for the market potential of the said fruits. The computed income elasticities for banana, durian, mango, and pomelo were -1.459, -0.00003, -1.169, and -0.027, respectively. The negative income elasticities indicate that banana, mango, durian, and pomelo have no market potential.
Thesis, Undergraduate (BS Economics)--University of the Philippines, Mindanao
Keywords: Banana trade -- Marketing -- Mindanao, Southern (Philippines); Durian industry -- Marketing -- Mindanao, Southern (Philippines); Mango industry -- Marketing -- Mindanao, Southern (Philippines); Grapefruit industry -- Marketing -- Mindanao, Southern (Philippines); Strategic plans